Kako učenci zaznavajo medijsko nasilje - Pšunder, Majda; Cvek, Mihaela (Revija za elementarno izobraževanje, 2009)
How pupils perceive media violence. In the modern information society media has become an integral part of peoples' and pupils' everyday life. Along with the many positive effects of this, there are also numerous negative ones, such as violence. Violence in the media influences the receivers - pupils. The most alarming consequences of pupils' frequent contact with media violence are imitation and apathy . Our survey, carried out on pupils from the 4th-8th grades of different primary schools in Slovenia, shows how they perceive media violence in these modern times